The Effect Of Product Attributes And Location On Consumer Purchasing Decisions (Survey of JSP Kids and Baby Product Consumers at Asia Plaza Tasikmalaya) - Hartoyo, Triaji; Arisman, H Ari; Lestari, Suci Putri (Universitas Dehasen Bengkulu, 2024)
This research aims to determine and analyze the influence of product attributes and location, both simultaneously and partially, on consumer purchasing decisions for JSP Kids and Baby Fashion products at Asia Plaza Tasikmalaya. The method used in this research is a survey. With a research sample of 97 consumers as respondents. The data used is primary and secondary data. The analytical tool used in this research is multiple linear regression using the SPSS version 25 support application. The test results show that simultaneously the variables used in the research, namely product attributes and location, have a significant effect on consumer purchasing decisions for JSP Kids and Baby Fashion products at Asia Plaza Tasikmalaya. Likewise, partially there is a significant influence of product attributes on purchasing decisions, and partially there is a significant influence between location on consumer purchasing decisions for JSP Kids and Baby Fashion products at Asia Plaza Tasikmalaya.